2019
DOI: 10.1111/hdi.12762
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between clinical judgment and integrated lung and inferior vena cava ultrasonography for dry weight estimation in hemodialysis patients

Abstract: Introduction: Correct dry weight estimation is very crucial for hemodialysis (HD) patients to maintain euvolemia. Most dialysis centers practice clinical judgment for dry weight estimation, which is subjective and can differ significantly from the actual weight. We designed this study to redefine the clinically estimated dry weight of patients on HD using integrated lung–inferior vena cava (IVC) ultrasonography (USG) and compare the symptoms arising due to volume overload and/or volume depletion before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…B-lines were defined as an echogenic, coherent, dynamic, wedge-shaped signal with a narrow origin in the near field of the image arising from the pleural line and extending to the screen’s edge [6]. TBLN ≥4 suggests increased EVLW [4]. In this study, we performed the analyses using the full cohort and a subcohort in which participants were found to have ≥4 TBLN at predialysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B-lines were defined as an echogenic, coherent, dynamic, wedge-shaped signal with a narrow origin in the near field of the image arising from the pleural line and extending to the screen’s edge [6]. TBLN ≥4 suggests increased EVLW [4]. In this study, we performed the analyses using the full cohort and a subcohort in which participants were found to have ≥4 TBLN at predialysis.…”
Section: Methodsmentioning
confidence: 99%
“…There is no consensus regarding the optimal method of extracellular volume assessment in HD patients [2, 3]. Volume assessment is usually based on clinical judgment [4], but dry weight estimation is subjective and can often be inaccurate and differ significantly from the actual dry weight.…”
Section: Introductionmentioning
confidence: 99%
“…Experts’ comments [ 66 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ]: Studies concerning dialysis patients most frequently follow the protocol of assessing 28 scans of the anterolateral chest, adapted from cardiologic examinations. The interpretation of the examination results is sometimes modified by resigning from the notion of “mild congestion”.…”
Section: Recommendationsmentioning
confidence: 99%
“…7 They propose dry weight reduction guided by 8-zone LUS with 2 anterior and 2 lateral zones in each hemithorax which, in conjunction with inferior vena cava assessment, was shown to decrease symptoms of dyspnea among patients with ESKD on HD. 8 A similar protocol among outpatients with chronic heart failure showed that patients in the highest tertile of B-lines had a 4-fold increase in the composite outcome of heart failure hospitalization or all-cause mortality. 9 pulmonary congestion, quantified using a further simplified 4zone LUS, was shown to decrease with diuretic therapy and identified patients at risk for adverse events in-hospital and on discharge among patients hospitalized with acute decompensated heart failure.…”
Section: Introductionmentioning
confidence: 99%